Using Augmented Reality To Make People Aware Of The Importance Of Managing Waste Through The Tiktok Social Media Application - Dimas Tri Danuarta; Hadi Irfanzha Prayoga; M Ikhsan Tanviry; Supina Batubara (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Waste management has become hot news in Indonesia and is increasingly urgent to be resolved. In an effort to make Indonesian people aware of the importance of their role in managing waste, especially the younger generation, information and communication technology can be an effective tool. One platform that is popular among teenagers is the social media TikTok, a social media application based on videos, images and audio. Exploring the use of Augmented Reality (AR) technology in the context of the TikTok application to increase public awareness about the importance of managing waste through the use of creative and interactive AR filters, this has had a positive impact in increasing Indonesian society's understanding and awareness of the waste problem and the steps that should be taken. taken to resolve it. This shows that the use of AR in the TikTok application can be a very effective tool for spreading environmental messages and encouraging positive behavior regarding waste management among all generations. Practical and theoretical implications in this regard are discussed as well as recommendations for further development in utilizing AR technology or Augmented Reality in the context of social media for the purpose of protecting the environment from waste.